ACTUAL PROBLEMS OF CONSERVATION OF THE INTANGIBLE CULTURAL HERITAGE IN THE CONTEXT OF EURASIAN INTEGRATION - Aktoty Raimkulova (Academic Journal of Physical and Chemical Sciences, 2020)
The Eurasian cultural space today is based on the thousand-year history of the joint existence of different ethnic groups and peoples. Shared values that ensure the stability of the cultural ties system are intensive intercultural interaction and recognition of the intrinsic value of all ethnocultural phenomena of many continent’s regions. Of crucial importance for a new round in the formation of the Eurasian community is culture. Due to the intensification of intercultural interaction in the 19th-20th centuries, a unique situation developed in Kazakhstan. At the same time various traditions together make up a single cultural system: folklore, the work of professionals of the oral tradition (zhyrau, akyns, kuishi, etc.), the national composer school, as well as mass music. One of the first researchers who not only discerned the similarities of the cultures of Eurasia in the 1920-1930s but also made considerable efforts to recognize the common cultural space of European and Kazakh music at the world level was A.V. Zataevich. A Eurocentric approach, the features of which are conservation, conservation, selection, change (“improvement”), alienation, is characteristic for the research and political position regarding national art in the Soviet Union. In the process of creating a unified cultural space, it seems essential to shift the emphasis in ethnomusicological studies from a “hermetic” approach to tradition as a valuable phenomenon in the study of musical traditions in a broad cultural (musical oriental studies) context. Preservation of the intangible heritage in its living, not alienated from the natural environment of life in society, forms should become a pan-Eurasian task. Its most important component is the study of both the past of traditions and their current state.